Cytoxicity and Apoptotic Mechanism of Ruthenium(II) Amino Acid Complexes in Sarcoma-180 Tumor Cells - Lima, Aliny Pereira; Pereira, Flavia Castro; Pinheiro Almeida, Marcio Aurelio; Santos Mello, Francyelli Mariana; Pires, Wanessa Carvalho; Pinto, Thallita Monteiro; Delella, Flavia Karina [UNESP]; Felisbino, Sergio Luis [UNESP]; Moreno, Virtudes; Batista, Alzir Azevedo; Silveira-Lacerda, Elisangela de Paula (Public Library Science, 2014)
Over the past several decades, much attention has been focused on ruthenium complexes in antitumor therapy. Ruthenium is a transition metal that possesses several advantages for rational antitumor drug design and biological applications. In the present study, five ruthenium complexes containing amino acids were studied in vitro to determine their biological activity against sarcoma-180 tumor cells. The cytotoxicity of the complexes was evaluated by an MTT assay, and their mechanism of action was investigated. The results demonstrated that the five complexes inhibited the growth of the S180 tumor cell line, with IC50 values ranging from 22.53 mu M to 50.18 mu M, and showed low cytotoxicity against normal L929 fibroblast cells. Flow cytometric analysis revealed that the [Ru(gly)(bipy)(dppb)] PF6 complex (2) inhibited the growth of the tumor cells by inducing apoptosis, as evidenced by an increased number of Annexin V-positive cells and G0/G1 phase cell cycle arrest. Further investigation showed that complex 2 caused a loss of mitochondrial membrane potential; activated caspases 3, caspase-8, and caspase-9 and caused a change in the mRNA expression levels of caspase 3, caspase-9 as well as the bax genes. The levels of the pro-apoptotic Bcl-2 family protein Bak were increased. Thus, we demonstrated that ruthenium amino acid complexes are promising drugs against S180 tumor cells, and we recommend further investigations of their role as chemotherapeutic agents for sarcomas.